The first Cenozoic roproniid wasp from the Paleocene of Menat, France (Hymenoptera: Proctotrupoidea) - Romain Garrouste; Jean-Marc Pouillon; André Nel (European Journal of Taxonomy, 2016)
Paleoropronia salamonei gen. et sp. nov., the first Cenozoic Roproniidae, is described from the Paleocene of Menat (Massif Central, France) on the basis of its fore wing venation. The Roproniidae range between the Mesozoic and the present time. P. salamonei gen. et sp. nov. was perhaps a parasitoid on tenthredinid sawfly larvae, as these insects were present in the wasp fauna from Menat outcrop.